2020
DOI: 10.1039/c9gc03299a
|View full text |Cite
|
Sign up to set email alerts
|

Continuous flow synthesis of menthol via tandem cyclisation–hydrogenation of citronellal catalysed by scrap catalytic converters

Abstract: A continuous flow synthesis of menthol in a tandem system using catalysts derived from the ceramic core of scrap catalytic converters is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Menthol is a fine chemical, one of the most common aroma compounds with a worldwide demand of more than 25 000-30 000 metric tons per year. [1][2][3][4][5] Three asymmetric carbon atoms in the cyclohexane ring lead to a chiral compound exhibiting four diastereoisomeric pairs, namely (±)-menthol, (±)-neomenthol, (±)-isomenthol and (±)-neoisomenthol. Only (−)-menthol has a strong physiological cooling effect and the characteristic odour worthy to be commercially used in i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Menthol is a fine chemical, one of the most common aroma compounds with a worldwide demand of more than 25 000-30 000 metric tons per year. [1][2][3][4][5] Three asymmetric carbon atoms in the cyclohexane ring lead to a chiral compound exhibiting four diastereoisomeric pairs, namely (±)-menthol, (±)-neomenthol, (±)-isomenthol and (±)-neoisomenthol. Only (−)-menthol has a strong physiological cooling effect and the characteristic odour worthy to be commercially used in i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The other seven isomers are typically considered less valuable. [1][2][3][5][6][7][8][9] Synthetic (−)-menthol is mainly obtained by the industrial Takasago five step process with myrcene as the main reactant. 7,[10][11][12] The last two steps in this process are the 'ene' cyclization of (+)-citronellal to (−)-isopulegol in the presence of Lewis acid aqueous ZnBr 2 catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, scanning transmission electron microscope high-angle annular dark-field (STEM-HAADF) imaging of the PW-TWC indicated that neither leaching nor aggregation of palladium had occurred after 8 h of reaction. Additional research by the Luque group has expanded on their work on PW-TWC, applying material derived from scrap to the continuous in-flow synthesis of menthol from citronellal [111]. The PW-TWC sample was employed both as a solid support for iron oxide nanoparticles (Fe-PW-TWC) to catalyse the cyclisation of citronellal and as a catalyst for the hydrogenation of (−)-isopulegol (Figure 16).…”
Section: Figurementioning
confidence: 99%
“…Another example is the tandem cyclization–hydrogenation that was exploited to synthesize menthol from citronellal by Luque and co‐workers . The developed Lewis acid catalyst consisted of supporting iron oxide nanoparticles on the ceramic core of SCATs.…”
Section: Continuous‐flow Hydrogenation Using Heterogeneous Catalystsmentioning
confidence: 99%